Sequence-based identification of microbial pathogens: a reconsideration of Koch's postulates. - Fredericks, D N (1996)
Over 100 years ago, Robert Koch introduced his ideas about how to prove a causal relationship between a microorganism and a disease. Koch's postulates created a scientific standard for causal evidence that established the credibility of microbes as pathogens and led to the development of modern microbiology. In more recent times, Koch's postulates have evolved to accommodate a broader understanding of the host-parasite relationship as well as experimental advances. Techniques such as in situ hybridization, PCR, and representational difference analysis reveal previously uncharacterized, fastidious or uncultivated, microbial pathogens that resist the application of Koch's original postulates, but they also provide new approaches for proving disease causation. In particular, the increasing reliance on sequence-based methods for microbial identification requires a reassessment of the original postulates and the rationale that guided Koch and later revisionists. Recent investigations of Whipple's disease, human ehrlichiosis, hepatitis C, hantavirus pulmonary syndrome, and Kaposi's sarcoma illustrate some of these issues. A set of molecular guidelines for establishing disease causation with sequence-based technology is proposed, and the importance of the scientific concordance of evidence in supporting causal associations is emphasized.